2015
DOI: 10.1007/s10464-015-9749-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Communities That Care on Males’ and Females’ Drug Use and Delinquency 9 Years After Baseline in a Community‐Randomized Trial

Abstract: This study tested sustained effects of the Communities That Care (CTC) prevention system on health-risking behaviors 9 years after baseline in a community-randomized trial involving 24 towns in seven states. Earlier analyses found sustained effects on abstinence from drug use and delinquency through Grade 12 in a panel of fifth graders. At age 19, 91 % (n = 3986) of the living panel completed the survey. Data were analyzed using generalized linear mixed models. The prevalence of lifetime and current substance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 62 publications
2
15
0
4
Order By: Relevance
“…The current findings add to a growing literature addressing this gap and indicate the potential benefits of developmentally well-timed interventions in early adolescence for substance-related outcomes during emerging adulthood, further substantiating results concerning substance misuse presented in our earlier reports from other projects (Spoth et al 2009 b , 2014 a , 2014 b ), and from other research groups that have reported results into young adulthood (Oesterle et al 2015). …”
Section: Discussionsupporting
confidence: 87%
“…The current findings add to a growing literature addressing this gap and indicate the potential benefits of developmentally well-timed interventions in early adolescence for substance-related outcomes during emerging adulthood, further substantiating results concerning substance misuse presented in our earlier reports from other projects (Spoth et al 2009 b , 2014 a , 2014 b ), and from other research groups that have reported results into young adulthood (Oesterle et al 2015). …”
Section: Discussionsupporting
confidence: 87%
“…For example, policy changes implemented in 2012 may have had a lesser impact on outcomes during the study period; however, those policy changes may be more impactful in subsequent years. Other research focused on supporting improvements in community-level prevention outcomes using measures from the CTC survey has shown that it may take 2 to 5 years to modify risk and protective factor outcomes, and 4 to 10 years before community-level impact on adolescent substance use may be observed (Oesterle et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Thus, adequate management strategies allow the operative differentiation of core components and secondary aspects of a program. Therefore, it is an alternative strategy for local adaptation of interventions, comparable to those that have been developed in other cases through participatory selection of evidencebased practices (Oesterle et al, 2015;Worton et al, 2014).…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%